Does any Artemisia species other than A. annua have potential to produce artemisinin? (Open Access Journal of Medicinal and Aromatic Plants, 2011)
(Abstract selected from presentation in National Conference on Biodiversity of Medicinal and Aromatic Plants: Collection, Characterization and Utilization, held at Anand, India during November 24-25, 2010) Â Artemisinin is one of the most effective medicines against malaria. This medicine is naturally produced only by Artemisia annua plants, but its production is low in its natural state. The introduction of related species with higher artemisinin contents has been suggested as an alternative. In this regard, 10 Artemisia species grown in Iran, were investigated. The experiments were carried out using PCR technique and specific primers based on the published am1 gene sequence from A. annua (NCBI, accession number AF327527). This gene encodes amorpha-4, 11-diene synthase (ADS), a key enzyme in artemisinin biosynthesis pathway. The amplification of this gene by specific primers was considered as a positive sign for the potentiality of artemisinin production. Since the entire am1 gene was not amplified in any of the 10 species used, four parts of the gene, essential in ADS enzyme function, encoding a) pair site of Arg10-Pro12 in the first 100 amino acids, b) aspartate rich motif (DDXXD), c) active site final lid and d) active site including farnesyl diphosphate (FDP) ionisation site and catalytic site, were investigated. The sequence corresponding to ADS active site was amplified only in A. annua, A. aucheri and A. chammelifolia. The negative results obtained with other species could be due to some sequence alterations, such as point mutations or INDELs. We propose A. aucheri and A. chammelifolia as two potential candidate species for further characterization, breeding and transferring am1 gene with the aim of enhanced artemisinin production.